Conceptualization, measurement and correlates of dementia worry: A scoping review. (January 2021) - Werner, Perla; AboJabel, Hanan; Maxfield, Molly
Highlights: A scoping review of 45 articles on dementia worry was carried out. A clear, consistent definition of the concept is lacking, as are validated scales. Gender, exposure to dementia, and psychological factors, are the main correlates. A consensual definition is needed to advance research and clinical knowledge. Abstract: Purpose: The combination of a growing population of older adults and increasing prevalence and awareness of dementia diagnoses suggests that dementia worry may also intensify. As a relatively new area of investigation, the dementia worry literature is growing, but variability in definitions and measurement continue. A scoping review was conducted to gather and examine existing research, as well as assist in guiding future studies in this area. The review focused on characterizing the conceptualization, measurement, and correlates of dementia worry. Methods: Using PubMed, CINAHL, AgeLine, and PsycINFO, a search of literature concerning dementia worry was completed. Results: A total of 45 articles examining dementia worry fulfilled the inclusion criteria. Most studies were cross-sectional (n = 39), quantitative (n = 38), and conducted in the United States (n = 22). Inconsistencies in the conceptualization, measurement, and correlates examined make it difficult to determine the meaning and true levels of dementia worry. Conclusions: Recent attention to dementia worry has increased awareness of the basic concept and its correlates. However, the lack of unity in the definition and measurement of dementia worry impedes advancement in this research area, as well as in establishing its clinical significance.